URGENSITAS, KEADILAN DAN MAQASID SYARIAH PADA MERGER BANK SYARIAH - Abd. Akram H; Citra Sukmadilaga; Lucky Nugroho (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to analyze the merger process of Islamic banks in Indonesia from the aspect of urgency, conformity with sharia principles, and maqasid sharia. The method used is descriptive quantitative by using secondary data as a basis for research analysis. Furthermore, the discussion of this research is limited by the formulation of the problem, which includes (i) What is the urgency of the merger of Islamic banks in Indonesia?; (ii) How is the suitability of the merger of Islamic banks in Indonesia with sharia principles?; (iii) What are the benefits of a sharia bank merger in Indonesia from the perspective of maqasid sharia?. Based on the study results, the current Islamic bank merger process is still at an early stage and needs strategic steps further, especially how to increase the market share of Islamic banks and the implementation of justice aspects in the merger process. Therefore, the merger process must also benefit the internal employees of Islamic banks whose banks have been merged and for the Islamic banking industry so that there is no monopoly on Islamic financial services.